Principles of therapeutic exercise for the physical therapist assistant - Kopack, Jacqueline Klaczak PT, DPT; Cascardi, Karen A. PhD, MS, ATC, PTA (Core texts for PTA education, 2023)
"Principles of Therapeutic Exercise for the Physical Therapist Assistant is a textbook that provides PTA educators, PTA students, and practicing PTA clinicians with a guide to the application of therapeutic exercise across the continuum of care.Written by two seasoned clinicians with more than 40 years of combined PTA education experience, Principles of Therapeutic Exercise for the Physical Therapist Assistant focuses on developing the learners' ability to create effective therapeutic exercise programs, as well as to safely and appropriately monitor and progress the patient within the physical therapy plan of care. The content is written in a style conducive to a new learner developing comprehension, while still providing adequate depth as well as access to newer research.Included in Principles of Therapeutic Exercise for the Physical Therapist Assistant are:Skill competency outlines, worksheets and problem-solving rubricsIndications, contraindications, and red flags associated with various exercise interventionsDocumentation tipsEasy-to-follow tables to aid in understanding comprehensive treatment guidelines across the phases of rehabilitation "Eye on the Research" sections throughout the text dedicated to current research and evidence-based practicesAlso included with the text are online supplemental materials for faculty use in the classroom, consisting of PowerPoint slides and an instructor's manual (complete with review questions and quizzes).Created specifically to meet the educational needs of PTA students, faculty, and clinicians, Principles of Therapeutic Exercise for the Physical Therapist Assistant is an exceptional, up-to-date guidebook that encompasses the principles of therapeutic science across the entire continuum of care"--